Principal Leadership Behavior Impact on The Character Education - Hanafiah Hanafiah; Ramazan Ramazan (STKIP Singkawang, 2022)
The principal as the leader directly is a real example in the work activities in the school environment. This study aims to look at the principal's leadership behavior, the relationship between the principal's leadership behaviors towards strengthening the character education of vocational students. This research uses a quantitative approach, using a cross-sectional survey method. The results of this study are based on the results of data processing obtained that five school principals have good leadership behavior with a percentage of 55.56%, and four school principals have reasonably good behavior with a percentage of 44.44%. Partial test results obtained there is a relationship between the principal's leadership behavior towards strengthening the character education of vocational students on the east coast of Aceh, principal's leadership behavior 58.8% to the student's character education. Based on the results of data processing, it is obtained that from 9 vocational high schools in the eastern part of Aceh that were studied, 5 schools (55.56%) principals had good leadership behaviors, and 4 schools (44.44 %) the principal has a fairly good leadership behavior. From the partial test results obtained that there is a relationship between the principal's leadership behaviors towards the education of the character strengthening of vocational students on the coast of East Aceh.